Specificity and current trends in the digital advertising development - A. V. Veretyokhin (Вестник университета)
The digital advertising development features and prospects in the world and in the Russian Federation in particular have been considered. An approach to defining the advertising concept essence in the digital field has been presented. A summary of the scientific research results has made it possible to identify the industry’s growth constraints and its main development drivers, as well as define the importance and distinguishing features of modern advertising campaigns in the digital space. Based on analysis of current data from relevant organisations for the digital advertising market, an increase in growth rates has been identified overall by region and country, as well as for individual advertising segments.